Analysis of Factors Causing Delays in Construction Projects in Balikpapan from the Project Management Perspective - Kartini, Dwi Aneka; Hakim, Afif Taufiiqul; Huzair T, Muhammad (Faculty of Science and Technology University of Pramita Indonesia, 2025)
Construction projects in Balikpapan face various challenges that hinder timely progress. This study aims to analyze the factors causing delays in construction projects in the area from a project management perspective. Based on data collected from various construction projects in Balikpapan, it was found that the main factors causing delays include planning errors, delays in material delivery, design changes, and lack of coordination among teams. The research method used was a questionnaire distributed to project managers and construction teams. Data analysis was performed using descriptive statistics to identify the dominant factors affecting project delays. The results show that poor time management and inadequate planning are the two most dominant factors causing delays. This study provides valuable insights for industry stakeholders in Balikpapan to improve managerial processes and enhance the efficiency of construction project execution.